2016
DOI: 10.1038/srep22958
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial communities of the cotton aphid Aphis gossypii associated with Bt cotton in northern China

Abstract: Aphids are infected with a wide variety of endosymbionts that can confer ecologically relevant traits. However, the bacterial communities of most aphid species are still poorly characterized. This study investigated the bacterial diversity of the cotton aphid Aphis gossypii associated with Bt cotton in northern China by targeting the V4 region of the 16S rDNA using the Illumina MiSeq platform. Our sequencing data revealed that bacterial communities of A. gossypii were generally dominated by the primary symbion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
46
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 45 publications
(56 citation statements)
references
References 56 publications
(71 reference statements)
7
46
3
Order By: Relevance
“…Eight bacterial groups, including Arsenophonus , Serratia , Rickettsia , and Wolbachia were cocolonized on Colocasia esculenta and Alpinia purpurata across the four Hawaiian Islands (Jones, Bressan, Greenwell, & Fierer, ). In this study, the relative abundances of 22 identified genera were more than 0.1%, including the three most abundant bacterial genera Arsenophonus , Hamiltonella and Acinetobacter and the three genera with low abundance ( Pseudomonas , Burkholderia , Stenotrophomonas ) that have been reported in A. gossypii (Jones et al., ; Najar‐Rodriguez et al., ; Zhao et al., ). None of the aphids surveyed were infected with the main endosymbiotic types ( Serratia symbiotica , Regiella insecticola , Rickettsia , Spiroplasma ) that were previously reported for other aphid species (Russell, Latorre, Sabater‐Munoz, Moya, & Moran, ).…”
Section: Discussionmentioning
confidence: 48%
See 4 more Smart Citations
“…Eight bacterial groups, including Arsenophonus , Serratia , Rickettsia , and Wolbachia were cocolonized on Colocasia esculenta and Alpinia purpurata across the four Hawaiian Islands (Jones, Bressan, Greenwell, & Fierer, ). In this study, the relative abundances of 22 identified genera were more than 0.1%, including the three most abundant bacterial genera Arsenophonus , Hamiltonella and Acinetobacter and the three genera with low abundance ( Pseudomonas , Burkholderia , Stenotrophomonas ) that have been reported in A. gossypii (Jones et al., ; Najar‐Rodriguez et al., ; Zhao et al., ). None of the aphids surveyed were infected with the main endosymbiotic types ( Serratia symbiotica , Regiella insecticola , Rickettsia , Spiroplasma ) that were previously reported for other aphid species (Russell, Latorre, Sabater‐Munoz, Moya, & Moran, ).…”
Section: Discussionmentioning
confidence: 48%
“…TIANamp Genomic DNA Kits (TIANGEN Biotech (Beijing) LTD., China) were used for DNA extractions. The protocol that was followed has been previously reported (Zhao et al., ). The quantity and quality of the DNA were measured with a NanoDrop 2000C spectrophotometer (Thermo Scientific, USA).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations